Avaliação da resistência à chamas de compósitos poliéster isoftálico insaturado com resíduo de lama vermelha e fibra de bambu - LIMA, Haianny Beatriz Saraiva (2022)
Polymeric matrix composite materials were manufactured with the insertion of natural bamboo fibers and industrial waste of red mud from the bauxite processing industry, taking into account sustainability, the wide availability of plant fibers in the Amazonia and the problem of industrial waste that can, through bad disposition, generate great environmental impacts. The production followed the manual manufacturing method hand lay-up in a silicone mold with pressure, with a mass percentage of 5 % for natural fibers in the size of 30 mm, and 20 % and 40 % for the industrial waste that passed through the process. of beneficiation obtaining granulometry of 325 Mesh from the Tyler series. The matrix used was unsaturated isophthalic polyester resin, with cobalt accelerator in the proportion of 1,5 % v/v and butanox M-50 catalyst in the proportion of 1 % v/v. The micrographic analysis of the fiber and residue was performed using a Scanning Electron Microscope (SEM) with Dispersive Energy System (EDS). After the preparation of the specimens, the physical tests of water absorption, apparent porosity and apparent specific mass were carried out according to ASTM D 570, ASTM D 2734 and ASTM D 792 standards. The flame propagation rate was determined through the horizontal flammability test (ASTM D 635) and, finally, the mechanical flexural strength test (ASTM D 790) was carried out with fracture surface analysis through MEV. The microstructural analysis showed particularities of the reinforcements, being possible to observe pores and roughness present in the fibers, as well as the morphology of the residue and different particle sizes. The Energy Dispersive Spectroscopy (EDS) showed some elements present in the residue. In the physical tests, an increase in water absorption and apparent porosity was observed as the reinforcements (fiber and residue) were inserted. In the flammability tests, excellent results were noted in the flame retardancy for the composites with the insertion of the residue in the matrix, with emphasis on the mass fraction of 40 % of red mud that extinguished the flame. In the bending test the composites obtained better results than the full matrix. Through fractographic analysis, noted the presence of cracks, pores, bubbles, as well as a mechanism of displacement and fiber pullout. The manufactured materials are candidates in some applications, such as wall partitions, panels and materials that don’t require high mechanical effort, thus attributing usefulness to a residue that in principle would be discarded, degrading the environment.